Implementation of Teacher Certification and Teacher Professional Education (PPG) and Challenges in Developing the Quality of Islamic Education - Sabrina, Ainah; Yuliharti, Yuliharti; Hasyim, Hariza (UIR Press, 2026)
To ensure the quality of education, the Indonesian government has taken various measures through a range of programs, both educational and non-educational. However, the strategies implemented have not been fully integrated, so special programs are considered necessary to strengthen teacher professionalism. This study aims to analyze regulations, government policies, and literature related to teacher certification and PPG to explain their role in improving teachers' professional competence, especially in developing the quality of Islamic education. This study applies a qualitative literature review approach in examining various laws and regulations as well as relevant academic literature. It analyzes regulations, academic literature, and government policies related to teacher certification and PPG. The results of the study explain that the certification and PPG programs have an important role in increasing the professional competencies that teachers should have. This can be done through strengthening the curriculum, competent human resources, teaching and learning facilities and infrastructure, and field experience. The implementation of PPG has proven to be able to produce competent, certified, and competitive teachers, thereby contributing significantly to the development of education quality, especially Islamic education in Indonesia.